Sexual Function in Men with Lower Urinary Tract Symptoms and Prostatic Enlargement Secondary to Benign Prostatic Hyperplasia: Results of a 6‐Month, Randomized, Double‐Blind, Placebo‐Controlled Study of Tadalafil Coadministered with Finasteride. (29th October 2014) - Glina, Sidney; Roehrborn, Claus G.; Esen, Adil; Plekhanov, Alexey; Sorsaburu, Sebastian; Henneges, Carsten; Büttner, Hartwig; Viktrup, Lars
Abstract Introduction Tadalafil (TAD) 5 mg coadministered with finasteride (FIN) 5 mg significantly improves lower urinary tract symptoms (LUTS) in men with benign prostatic hyperplasia (BPH) and prostatic enlargement. However, its effects on erectile/sexual function have yet to be fully described. Aim Assess the effects of TAD/FIN coadministration (compared with placebo [PBO]/FIN) on erectile and sexual function in sexually active men with LUTS and prostatic enlargement secondary to BPH with or without baseline comorbid erectile dysfunction (ED). Methods A randomized, double‐blind, PBO‐controlled study of 695 men (610 sexually active; 450 with baseline ED; 404 sexually active with baseline ED) conducted at 70 sites in 13 countries. TAD 5 mg or PBO once daily coadministered with FIN 5 mg once daily for 26 weeks. Main Outcome Measures International Index of Erectile Function (IIEF) domain and single‐item scores; proportions of patients who demonstrated minimal clinically important differences (MCIDs) in IIEF‐Erectile Function domain scores (IIEF‐EF; MCID defined as ≥4‐point improvement); and sexual dysfunction adverse events (AEs). Results Compared with PBO/FIN, TAD/FIN resulted in improvements for all IIEF domain and single‐item scores assessed among patients with baseline ED (P ≤ 0.002 for all measures) and among patients without baseline ED (P ≤ 0.041 for all measures). Compared with PBO/FIN, significantly larger percentages of sexually active men with baseline ED treated with TAD/FIN achieved an IIEF‐EF MCID after 4, 12, and 26 weeks of therapy (P < 0.001 for odds ratio comparisons between TAD/FIN and PBO/FIN at all 3three postbaseline timepoints). The incidence of sexual AEs was low: five TAD/FIN patients and seven PBO/FIN patients reported sexual AEs, including ED, decreased/lost libido, and ejaculation disorders. Conclusions TAD/FIN coadministration for the treatment of men with LUTS and prostatic enlargement secondary to BPH concurrently leads to statistically significant improvements in erectile/sexual function and is well‐tolerated, regardless of the presence/absence of ED at treatment initiation. Glina S, Roehrborn CG, Esen A, Plekhanov A, Sorsaburu S, Henneges C, Büttner H, and Viktrup L. Sexual function in men with lower urinary tract symptoms and prostatic enlargement secondary to benign prostatic hyperplasia: Results of a 6‐month, randomized, double‐blind, placebo‐controlled study of tadalafil coadministered with finasteride. J Sex Med 2015;12:129–138.